Tearoom trade : impersonal sex in public places - Humphreys, Laud (Transaction Publishers, 2008)
From the time of its first publication in 1970, this book engendered controversy. It was also accorded an unusual amount of praise for a first book on a marginal, intentionally self-effacing population by a previously unknown sociologist. The book was quickly recognized as an important, imaginative, and useful contribution to our understanding of "deviant" sexual activity. Describing impersonal, anonymous sexual encounters in public restrooms - "tearooms" in the argot - the book explored the behavior of men whose closet homosexuality was kept from their families and neighbors. By combining participant observation with structured as well as informal interviews, Tearoom Trade still furnishes a controversial example of recent social science methods. This enlarged edition includes the original text, together with a retrospect. The material added includes a perspective on the social scientist at work and the ethical problems to which that work may give rise, along with debate by t.